The Influence of Accounting Management Capabilities on the Success of Small and Medium Enterprises (SMEs) in Northeastern Thailand - Klongkaeo, Nanichakorn; Pongwiritthon, Kajornatthapol; Pudjaiyo, Nunticha; Chetkhunthod, Palida (RATANABUTH JOURNAL, 2025)
This study aimed to 1) analyze the relationship between accounting management capabilities and the success of Small and Medium Enterprises (SMEs) in Northeastern Thailand; 2) examine the influence of accounting management capabilities on the success of SMEs in Northeastern Thailand; and 3) investigate the causal relationships of factors influencing the success of Small and Medium Enterprises (SMEs) in Northeastern Thailand. Data were collected from 400 accountants of Small and Medium Enterprises (SMEs) in the region. A questionnaire was used as the research instrument, and the data were analyzed using multiple correlation analysis and multiple regression analysis. The results revealed that, 1) Accounting management capabilities were significantly related to the success of small and medium enterprises (SMEs) in Northeastern Thailand. 2) Accounting management capabilities, including bookkeeping, account closing, financial communication and reporting, and the utilization of accounting information, had a positive influence on the success of SMEs in the region and 3) The success of Small and Medium Enterprises (SMEs) in Northeastern Thailand was most positively influenced by the utilization of accounting information, with the highest positive effect coefficient observed.